Tumour cytotoxic agent and methods thereof. - Foo, Hooi Ling; Loh, Teck Chwen; Chuah, Li Oon; Mohammed Alitheen, Noorjahan Banu; Abdul Rahim, Raha (2012)

(untitled)
The present invention discloses a novel antitumor agent which provides an antitumor activity based on metabolites with reduced side effects. Moreover, the antitumor agent is prepared starting with a highly safe bacterium used in food production, which is a probiotic lactic acid bacterium.